(3eYQaI GdYjf hWHbGJgG hCSeGFgG heLGQjgGs - (3jhMfG Hf eGShjg, CHh RcQjG,J (B243 (3g` s ((3YHO GdQMef Hf jhfS Hf CHj GdMSf GdCfUGQi s)
(3ChdgG (B:s
(3gPG cJGH eYQaI GdYjf hWHbGJgG heLGQjgG hCUhd JQcjHgG , heSGFd ai YddgG hGeJMGf ai cjajJgG hcjajI JQcjHgG s
(3BNQgG (B:s
(3hChQGe GdYUH hGdYQhb hfJhA dMe GdeBb hGdThGdjd hGfJTGQ GdCTaGQ hGdOeYI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B10 - (3U(B24s
(3LGA Ydi GdUaMI GdChdi YfhGf cJGH eMfI GdcMGdjfs
(3djMj Hf eGShjg GdeJWHHs
(3Yf fSNI cJHgG eYdeg GdMcje YHO GdQMef Hf EHQGgje Hf SGde Hf YeGO GdebOSi GdCfUGQi (B540(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs